Pemberdayaan kesehatan masyarakat Desa Gunung Manik Melalui Potensi Desa Budidaya Madu: Empowerment of community health in Gunung Manik Village through the Village Potential of Cultivating Honey - Kunaedi, Aan; Lestari, Trisna; Johan, Johan; Utami, Arie Susetio; Prasetyo, Tri Budi; Andriana, Andriana; Angela, Elva (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The abundant natural potential of Gunung Manik has not been optimally utilized. The support of the village apparatus to continue to improve village welfare makes the development of villages and residents quite fast in receiving positive information from outside. Natural potential can be further optimized, one of which is by developing honey cultivation, which has great potential with the support of available natural resource conditions. Activities are carried out using counseling methods and interactive directly to measure the level of pre-activity knowledge and understanding in the people of Gunung Manik Village, descriptive material presentation through interactive so that the implementation of activities is more active and avoids boredom. The results of the activity can be seen from increasing community insight into health, That is benefits of honey on health and the enthusiasm of community for honey cultivation as an effort to improve the economy and health of the people of Gunung Manik Village, Ciniru Kuningan.